Counting on quality in endoscopy globally: all that matters now - Ragunath, Krish (Translational Gastroenterology and Hepatology, 2018)
I appreciate that Drs. Cho and Chiu agree regarding the importance of defining quality standards in upper gastrointestinal endoscopy (1,2). However, a few points have been raised with regards to the position statement by the British Society of Gastroenterology (BSG) and the Association of Upper Gastrointestinal Surgeons of Great Britain and Ireland (AUGIS) (3).